Respuesta agronómica de cultivo de pimiento (Capsicum annum) con la aplicación de abonos orgánicos foliares y edáficos - Arias Montes, Ronald Alexander (2016)
This research was conducted at the Experimental Center "La Playita", Technical University of Cotopaxi, Canton La Mana. WGS 84 geographic location: Latitude S0 ° 56 '27 "W Longitude 79 ° 13' 25", height 120 meters. The objectives were to assess the effects of the application of foliar and soil in organic pepper plant fertilizers, evaluate indicators of pepper plant growth, determine the crop yield in pepper plants, setting the nutrient requirements in growing pepper, evaluate the economic analysis of the most promising treatments in pepper plants. one Full random design (CRD) with five treatments and five repetitions was used. The results, plant height treatments that are more highlighted Vermicompost 30 days Gallinaza 26.47 cm and 60 days, 65.93 cm, the largest number of fruits was obtained from humic acid fertilizer with 7 , 17 fruits....